The 2 meal day : burn fat and boost energy through intermittent fasting - Lowery, Max (Kyle Books, 2018)
In The 2-Meal Day, Max Lowery introduces intermittent fasting eat just two meals a day either breakfast and lunch or lunch and dinner to burn fat and get fit fast. Rather than grazing on food all day or having to do complicated calorie calculations for two days of the 5:2 diet, simply eat two meals to lose weight, reduce hunger and feel more energized. Choose your two meals from Max's delicious, nutritious and easy-to-prepare recipes; start the day with Salmon Mini Frittata or Raspberry Avocado Smoothie for breakfast; Lunch on Bacon Feta Omelette or Tuna Casserole or enjoy Chicken and Feta Meatballs, Sea Bass Sauce Vierge or Chicken Satay and Asian Slaw for Dinner. There are even healthier desserts to satisfy your sweet tooth without over-indulging choose from Two-Ingredient Chocolate Mousse or Banana 'Nicecream'. Max shows how to combine the two-meal day with High Intensity Interval Training (HIIT) plans, short duration and maximum effort exercises to help you drop fat and get fit quickly.